The Experience of Grace in The Phenomenon of Interreligious Dialogue - Herwindo Chandra (Asosiasi Ahli Filsafat Keilahian Indonesia, 2022)
This paper explores the experience of grace in the interreligious dialogue activists. The involvement of Catholic activists in this movement can be a locus for the experience of grace. Several theologians have recently discussed grace in a historical dimension. One of the theologians of the Second Vatican Council, Karl Rahner, had the idea of the experience of grace. Martin Heidegger's phenomenological hermeneutic method explores the experience of the grace of Catholic activists. In-depth interviews were used as a data collection technique. The research subjects were two Catholics, the National Meeting of Indonesian Youth from the Youth Commission of the Indonesian Bishops' Conference and one Catholic Young Interfaith Peacemaker Community. The results' novelty shows that the research subjects did not recognize grace as an extraordinary phenomenon. Inspired by the Church's teachings, they understand that grace is experienced as a process of living life's roles, unique abilities, and gifts to become better. The study’s conclusion confirms that grace can be identified in everyday life and is not limited to a superstructure metaphysical idea.